Solitons and Conservation Laws for the (2+1)-Dimensional Davey-Stewartson Equations with Conformable Derivative - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa; Baleanu, Dumitru (Amer Scientific Publishers, 2018)
This research obtains some new solitons for the Davey-Stewartson equation (DSE) with conformable derivative. The well known projective Ricatti equation ansatz (PREA) is employed to reach such solitons. The constraints conditions for the existence of soliton solutions are reported. Moreover, the conservation laws (Cls) for the governing equation is studied via multiplier technique. Physical features of some solutions are illustrated in Figures 1-8.
Keywords: DSE; PREA; Solitons; Conformable Derivative; Conservation Laws